Lecturers' Consideration in Developing Language Tests - Nur Fadillah Nurchalis; Ibrahim leman; Amzah Selle (EDUVELOP, 2018)
Abstract: This research aims to find out (1) the neglected variables of characteristics of a good test which is done by lecturers in developing their test, and (2) the ways the lecturers develop their own test in relation to the neglected variables. This research is explanatory mix method design. There are two variables in this research. They are lecturers’ consideration and test development. The population of this research is 33 lecturers in which 18 from IAIN Parepare and 15 from UMPAR. The samples are taken by random technique in which 30 samples. The instruments of this research are questionnaire, interview and documentation. This research uses percentage technique to analyze the data. The results of this research show that (1) here are the sequences of the neglected variables in developing language test: reliability, appropriateness in difficulty, clarity, comprehensiveness, validity, transparency, appropriateness in time, and economic, and (2) From three interview sections, this research finds differences of the way lecturers develop their test. They develop their test through challenging, creative and spontaneous test.